A case report navigating CVID and sarcoidosis overlaps in pediatric nephritis - Salih, Amanda; Brown, Amanda; Grimes, Amanda; Hasan, Sana; Silva-Carmona, Manuel; Tal, Leyat; Hajjar, Joud (Frontiers in Pediatrics, 2024)
Common Variable Immunodeficiency (CVID) can be complicated by granulomatous disease, often Granulomatous Lymphocytic Interstitial Lung Disease (GLILD). Granulomatous interstitial nephritis represents an atypical presentation in pediatrics. Our patient is a previously healthy 13-year-old Caucasian male with a recent diagnosis of CVID. He presented with rash and laboratory findings included pancytopenia (white blood cells 2.6 cells x 10^3/uL, hemoglobin 11.8 g/dL, platelets 60 x 10^3/uL), hypercalcemia (14.9 mg/dL), elevated Vit D 1,25 OH level (>200 pg/mL), hyperuricemia (8.8 mg/dL), and Acute Kidney Injury (AKI) (serum creatinine 1.1 mg/dL; baseline 0.64 mg/dL). A broad infectious workup was unremarkable. Rash improved with empiric doxycycline. Hypercalcemia and hyperuricemia were managed with fluid resuscitation, calcitonin, and zoledronic acid. Evaluation for malignancy including Positron Emission Tomography (PET) scan, revealed multiple mediastinal hypermetabolic lymph nodes and pulmonary ground glass opacities, later reported as small pulmonary nodules by Computer Tomography (CT). Splenomegaly was confirmed by ultrasound and CT. Peripheral smear, bone marrow biopsy, and genetic testing were non-revealing. The Angiotensin-Converting Enzyme (ACE) level was elevated (359 U/L), raising concerns for sarcoidosis. Given Stage 1 AKI, a renal biopsy pursued identified non-caseating granulomatous interstitial nephritis. Treatment with prednisone 60mg began for presumed sarcoidosis for four months causing steroid-induced hypertension and mood changes. Zoledronic acid minimally reduced serum creatinine. Pneumocystis jirovecii pneumonia prophylaxis was initiated due to T-cell cytopenia. Chest CT findings showed a suboptimal response to steroids. Bronchoalveolar lavage demonstrated >50% lymphocytes (normal <10%) and lung biopsy exhibited non-caseating granulomas indicating GLILD. Rubella was identified by stain. Following a fever, he was found to have elevated liver enzymes and confirmed hepatitis with portal hypertension on CT. A liver biopsy revealed epithelioid non-caseating granuloma and HHV6 detected by PCR. He was treated with four cycles of rituximab and Granulocyte-Colony Stimulating Factor (G-CSF) for persistent neutropenia. Subsequent treatment with mycophenolate led to resolution of granulomatous lesions and cytopenias. The rare complication of granulomatous interstitial nephritis in CVID illustrates the intricate nature of diagnosis. This case underscores the necessity for a holistic view of the patient's clinical and immune phenotype, including distinctive radiological presentations, for precise diagnoses and tailored management in CVID.